Underactuated tracking control of underwater vehicles using control moment gyros. (11th January 2018) - Xu, Ruikun; Tang, Guoyuan; Xie, De; Huang, Daomin; Han, Lijun
This article studies the trajectory tracking control of underactuated underwater vehicles using control moment gyros through a biologically inspired approach based on homeomorphism transformation and Lyapunov functions in the horizontal plane. First, a series of assumptions and simplifications need to be made to build the kinematic and dynamic equations of the underwater vehicle under a single-frame pyramid configuration structured with four control moment gyros. Second, the error dynamics analysis of the submarine based on the control moment gyros is derived from the equations, and a tracking control algorithm is proposed to demonstrate the feasibility and stabilization of this tracking control scheme from theoretical analysis. Finally, the numerical simulation results are given for verifying the effectiveness and feasibility of the rendered control law.